1994
DOI: 10.1021/bi00255a006
|View full text |Cite
|
Sign up to set email alerts
|

Drug Binding by Calmodulin: Crystal Structure of a Calmodulin-Trifluoperazine Complex

Abstract: The crystal structure of calmodulin (CaM) bound to trifluoperazine (TFP) has been determined and refined to a resolution of 2.45 A. Only one TFP is bound to CaM, but that is sufficient to cause distortion of the central alpha-helix and juxtaposition of the N- and C-terminal domains similar to that seen in CaM-polypeptide complexes. The drug makes extensive contacts with residues in the C-terminal domain of CaM but only a few contacts with one residue in the N-terminal domain. The structure suggests that substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
179
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(192 citation statements)
references
References 37 publications
13
179
0
Order By: Relevance
“…For example, troponin C binds two TFP molecules (PDB 1WRK) and calmodulin binds TFP with a range of stoichiometries; 1∶1 (PDB 1CTR), 1∶2 (PDB 1A29), and 1∶4 (PDB 1LIN) (28)(29)(30). Even though S100A4, troponin C, and calmodulin are built upon the same basic four-helical structural module, the architectures of the TFP binding pockets, and the positions and orientations of the bound TFP molecules are quite different amongst the three proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, troponin C binds two TFP molecules (PDB 1WRK) and calmodulin binds TFP with a range of stoichiometries; 1∶1 (PDB 1CTR), 1∶2 (PDB 1A29), and 1∶4 (PDB 1LIN) (28)(29)(30). Even though S100A4, troponin C, and calmodulin are built upon the same basic four-helical structural module, the architectures of the TFP binding pockets, and the positions and orientations of the bound TFP molecules are quite different amongst the three proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is a monotonic decline in actinactivated MgATPase (ϮCa 2ϩ ) that is complete at 300 M TFP, and prior removal of R-LC by EDTA still permits TFP inactivation of the desensitized myosin and exhibits the same concentration dependence (Fig. 3), suggesting that the heavy chain⅐E-LC complex can be induced to attain this extreme (12), as seen from the same perspective as for calmodulin (a); c, relationship of the putative TFP-binding site within E-LC as found within the smooth muscle myosin motor domain⅐E-LC ADP⅐AlF 4 Ϫ complex (35), illustrating its proximity to heavy-chain amino acid residues at the entrance to the nucleotide-binding pocket; d, relationship of the putative TFP-binding site within E-LC as found within scallop adductor myosin MgADP⅐S-1 (36), illustrating its proximity to heavy-chain amino acid residues within the SH3 domain. In c and d, perspectives were chosen to illustrate the proximity of the E-LC C-terminal TFP-binding lobe to key heavy-chain surface features; the view of the converter region, which maintains its relationship to E-LC in both structures (35), is approximately the same in both cases.…”
Section: Discussionmentioning
confidence: 86%
“…6). In the stoichiometric TFP⅐calmodulin complex, the hydrophobic tricyclic ring of TFP localizes to a hydrophobic pocket within the C-terminal lobe of calmodulin, entrapping TFP⅐calmodulin in the same conformation as that seen when calmodulin binds to a target peptide substrate (4,6,7). Although the C-terminal lobes of scallop R-LC and E-LC exhibit semi-open conformations, in contrast to the C-terminal lobe of calmodulin, which displays a fully open conformation (10), the required hydrophobic pocket remains available, albeit less deeply placed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a set of CaM antagonists including W-7 and W-9 has been generated from naphthalenesulfonamide derivatives (14). The recent elucidation of the crystal structure of the Ca 2+/CaM complex with trifluoperazine revealed that Ca 2+/CaM binds to the CaM antagonist in a similar shape to that observed in Ca 2+/CaM/M13 (9,15). Pharmacological studies by Hidaka and co-workers suggest that CaM is involved in platelet aggregation and secretion (16), vascular contraction (17), cell proliferation (18) and the degranulation of neutrophils (19).…”
mentioning
confidence: 90%